A comprehensive review of the development of Brazil’s asset management system aligned with ISO 55001 - Oliveira, Helton Luiz Santana (Brazilian Journal of Production Engineering, 2026)
This article presents an evolutionary perspective on asset management, tracing its development from the foundations of Terotechnology in the United Kingdom to the consolidation of the ISO 55001 standard and its incorporation in Brazil. It examines the historical, institutional, and regulatory factors that shaped the discipline, as well as current trends and challenges that influence the maturity of asset management systems across diverse contexts. The study adopts a historical-comparative approach that revisits pioneering British initiatives among them, the investigations promoted by the Ministry of Technology during the 1960s and 1970s and subsequently analyzes Australian contributions, particularly the production of manuals and the integration of asset management into regulatory frameworks. The Brazilian trajectory is also addressed, marked by the transition from corrective and preventive practices to more strategic models, with emphasis on the role of ABRAMAN and the adoption of ISO 55001. Evidence from the ISO Survey 2023 and the ABRAMAN 2022 national survey supports an assessment of global and national maturity. The findings indicate a progression from technical approaches toward a governance- and value-oriented perspective.